The Role of Helicobacter pylori in Induction of Gastric Autoimmunity - Sora J. Abd-Alsaheb,; Hasan Abd Ali Khudhair,; Khalid Majeed Dakhel, (University of Thi-Qar Journal of Science, 2023)
Introduction: Helicobacter pylori (H. pylori) is a member of the causative factors of digestive system complaints, such as gastritis, stomach ulcers, mucosal-associated lymphoid tissue lymphoma (MALT), and gastric cancer (GC). This research aimed to determine the H. pylori bacteria's possible roles in autoimmune gastritis (AIG) and assess the sera concentrations of vitamin B12 (VB12) and iron in individuals with and without H. pylori disease. Methods: In the Province of Thi-Qar, Iraq, case-control research was conducted during the time of November-2021 to June-2022, which included 55 subjects having H. pylori-associated diseases and 35 healthy individuals. The eligibility criteria of both study groups were followed stringently. For the patient's group, subjects underwent an endoscopic examination and a stool antigen test (SAT). Additionally, the subjects of all research cohorts were assessed for their sera levels of anti-H. Pylori-antibodies (Abs), parietal cells auto-Abs (PCA), VB12, and iron. Results: The findings revealed a significantly higher level of PCA positivity and lower levels of VB12 and iron by comparing the patient group with the control group. In both study groups, serum level of anti-H. pylori immunoglobulin gamma (IgG) Abs positively associated with PCA and inversely correlated with serum VB12 and iron in the patient's group. Conclusions: There were correlations between H. pylori infection and PCA-positive status, lower VB12, and low iron levels. Anti-H. pylori-IgG serum concentration was a valuable biomarker for the risk of developing AIG, low VB12, and iron levels. Parietal cells auto-Abs were not associated with VB12 and iron levels.